Contributing factors for participation and independence in children and youths with disabilities - Anna Karin Axelsson; Magnus Ivarsson; Henrik Danielsson; Anna Ullenhag (Scandinavian Journal of Occupational Therapy, 2024)
Background Disabilities can hinder children’s and youths’ participation (frequency of attendance and engagement) and independence in everyday life.Aims To identify factors that predict levels of participation and independence in everyday activities in Swedish children and youths with disabilities.Material and methods This cross-sectional study, including 131 participants, utilised instruments about child and environmental factors. LASSO regression analyses were conducted to identify predictors of participation and independence.Results An item screening for comprehension difficulties was the strongest predictor of attendance, engagement, and independence in daily activities. Other influential child factors included the presence of seizures, speech abilities, age, pain levels, and motor functions. None of the studied environmental factors were retained as predictors in the models.Conclusions Difficulties in intellectual functioning need to be evaluated and considered in planning interventions to improve participation and independence. Likewise, multifaceted nature of challenges found in this study underscores the need for diversity of interventions tailored for individual needs.Significance The result underscores the critical role of comprehension and intellectual functioning in predicting and enhancing participation and independence in children and youths with disabilities, advocating for comprehensive assessments and sustained support.